Experimental Study to Evaluate the Safety and Immunomodulatory Effect of Swarna Vacha Yog in Wistar Albino Rats - Rashmi Pareek; Nisha Kumari Ojha; Sanjeev Sharma (Journal of Ayurveda)
Introduction:Recently, concerns were raised about the safety of Ayurvedic medicines using Bhasma and concerns were expressed regarding the metal toxicity of traditional preparations containing Bhasmas. Hence, to analyze safety and immunomodulatory effect of an Ayurveda herbomineral preparation Swarna Vacha Yog, an experimental study was conducted in Wistar Albino Rats. The proposed formulation was intended for oral administration. Hence, the safety study was performed using OECD proposed Oral Toxicity Guidelines and was evaluated by response in Wistar Albino Rats.Methods:Nine healthy adult albino Wistar Albino Rats from both sexes were randomly selected for toxicity study which were divided into three groups (three in each group) and 24 selected randomly and divided in four groups for immunomodulatory effect.Results and Conclusion:No any evidence of acute toxicity was observed after giving test sample at dose of 50, 300 and 2000 mg/kg at 30 min, 4 h, 24 h, 48 h, 1 week, and 2 weeks. There was less reduction in total leukocyte count and neutrophil count (P < 0.0001) when trial drug was compared with normal control and standard control in cyclophosphamide-induced neutropenia rat model.